Breaking black-hole uniqueness at supermassive scales - Eichhorn, Astrid; Fernandes, Pedro Goncalo da Silva; Held, Aaron; Silva, Hector O. (Classical and quantum gravity, 2025)
In general relativity (GR), all asymptotically flat, stationary and axisymmetric vacuum black holes are described by the Kerr solution. Beyond GR, there is a prevailing expectation that deviations from the Kerr solution increase with the horizon curvature. We challenge this expectation by showing that, in a scalar-Gauss-Bonnet theory, black holes scalarize in a finite, adjustable window of black-hole masses, bounded from above and below. In this theory, there is an interplay between curvature scales and compactness, which we expect to protect neutron stars and other less compact objects from scalarization. In addition, this theory is the first to avoid the catastrophic instability of early-Universe cosmology that affects previous scalarization models. In this theory, black-hole uniqueness can be broken at supermassive black-hole scales, while stellar-mass black holes remain well-described by the general relativistic solution. To probe this scenario, observations targeting supermassive black holes are necessary.